Additional effects of core stability exercises on pain and function of patients with patellofemoral pain: A randomized controlled trial - Behnaz Tazesh; Mohammad Ali Mansournia; Farzin Halabchi (Journal of Orthopaedics, Trauma and Rehabilitation)
Background/purpose: Recently, there is more emphasis on the role of core muscles in pathogenesis and rehabilitation of patellofemoral pain (PFP). We aimed to investigate whether increased core muscle strength and endurance improve clinical outcomes. Methods: In a randomized controlled trial, 60 patients (M/F: 25/35, age = 32.28 (5.9) years) with PFP were randomly allocated into two groups of routine exercise (control) and combined core plus routine exercise (intervention). Home exercise was scheduled at least 5 times/week for 12 weeks. We assessed the outcomes of pain (Visual analogue scale) and function (Anterior knee pain score) before and immediately after interventions. Results: Significant improvements were reported in both groups (P < 0.001). There were significant between-group differences in both outcomes in favor of the intervention (Pain: 12.4, CI 95%: 7.1–17.8, P < 0.001; Function: 6.4, CI 95%: 2.2–10.5, P = 0.003). Conclusion: Outcome improvements were significantly greater in intervention group. Inclusion of core stability exercises may lead to additional benefits.